Statistical model structure of A₁₋xZxB₂ Laves phase C15 system - the superconducting Ce₁₋xLaxRu₂ alloy - Robouch, B.V.; Marcelli, A.; Saini, N.L.; Kisiel, A. (Физика низких температур, 2009)
Local structure of Ce₁₋xLaxRu₂ system, measured by EXAFS has been re-examined and correlated to the statistical ad hoc model, recently applied to the sphalerite, wurtzite and other intermetallic ternary alloys. The deconvolution of the EXAFS data show that the Ce₁₋xLaxRu₂ ternary system is essentially a mixture of: CeRu₂ and LaRu₂ binary alloys with a small proportion of the Ce₀.₅La₀.₅Ru₂ ternary configuration, being maximum for the intermediate concentration. Moreover, the analysis reveals that while the LaRu₂ configuration exhibits a Bernoulli random distribution, the presence of a Ce atom affects both the CeRu₂ and Ce₀.₅La₀.₅Ru₂ distributions, strongly favoring the configuration with the CeCe pair, while keeping rare that with a single Ce ion.